If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 7) + -6 = 2(x + 8) Reorder the terms: 3(7 + x) + -6 = 2(x + 8) (7 * 3 + x * 3) + -6 = 2(x + 8) (21 + 3x) + -6 = 2(x + 8) Reorder the terms: 21 + -6 + 3x = 2(x + 8) Combine like terms: 21 + -6 = 15 15 + 3x = 2(x + 8) Reorder the terms: 15 + 3x = 2(8 + x) 15 + 3x = (8 * 2 + x * 2) 15 + 3x = (16 + 2x) Solving 15 + 3x = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 15 + 3x + -2x = 16 + 2x + -2x Combine like terms: 3x + -2x = 1x 15 + 1x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 15 + 1x = 16 + 0 15 + 1x = 16 Add '-15' to each side of the equation. 15 + -15 + 1x = 16 + -15 Combine like terms: 15 + -15 = 0 0 + 1x = 16 + -15 1x = 16 + -15 Combine like terms: 16 + -15 = 1 1x = 1 Divide each side by '1'. x = 1 Simplifying x = 1
| -166-2344= | | 7/x-3 | | 7x+8=-7+92 | | 2(3x+5)=-14 | | -4x+7/3=8/3 | | 2(x+1)=8x | | 3v+8u+8v+9u= | | -5x+2=-1-2x | | f(x)=2x^2-5x+168 | | 4(2x+5)=3(x-6) | | -2n+9n-343=0 | | 10x-116=3x-11 | | 3a+5+(2a-3)= | | 7x+2+90+3x+-12=180 | | 6x+6+5x=50 | | 5x^2-29x=6 | | 3x-1=-7x+59 | | 4x+2-2x=-8 | | 5/3x+x=56 | | 12-5=n | | -3+3x=x-7 | | 7x+8=-7x+92 | | -a+3b-b+5a-6b= | | 5y+8=33 | | 10(x-8)=2x-20 | | 6=-3x+2x+5 | | 10-n=5 | | 33=x+7x+1 | | 60=-2(m+3)m | | 2x/x+4=8-8/x+4 | | 3(.75)=x | | 6x+5+5x=50 |